The International Labour Organisation - its origins and story - Stafford, Brigid (Statistical and Social Inquiry Society of Ireland, 1953)
This is a factual statement. It does not deal with such fascinating speculations as the extent to which the I.L.O. has contributed to the Welfare State, the effect of the creation of common denominators in hours of work and other conditions of employment, the alternative method, if any, to that provided in the Constitution for dealing with the dual authorities in Federal States, the inequality in the number of Government delegates for each State, viz., two as compared with one each for employers and workers, the advantages or disadvantages of detailed conventions compared with conventions confined to principles supplemented by recommendations embodying details, and finally the value of the new post-war activities of the I.L.O., particularly in the field of technical assistance.
Read before the Society, 12 June 1953
Keywords: International Labour Organisation; ILO; Labour standards; International labour history; 314.15